Reaction on the Johannesburg Stock Exchange to major shifts in dividend policy - Narendra Bhana (South African Journal of Business Management, 1991)
The objective of this article is to examine the share market response to substantial changes in dividend policies for companies listed on the Johannesburg Stock Exchange. The results provide strong support for the information content of dividend hypothesis. Investors revise their expectations in response to announcement of significant dividend changes. The market reacts more dramatically to negative than to positive dividend changes. The JSE appears to be inefficient in reacting to the announcement of dividend changes; economically significant abnormal returns are observed for a period of up to 20 trading days after the event. A systematic trader in dividend changing shares would have earned significant abnormal returns even though the market effects large corrections before, and at the announcement date. This pattern is especially clear around dividend omissions and large dividend decreases.
Keywords: 650